2018
DOI: 10.5812/jkums.68669
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcotaneus Electrical Acupoint Stimulation on Sleep Quality in Nurses

Abstract: Background: Sleep problems are one of the most common health problems in people with shift jobs. Due to being awake during night, nurses face with sleep problems, resulting in impaired cognitive functioning and professional mistakes. One of the common treatments in complementary medicine is transcutaneous electrical acupoint stimulation (TEAS). The purpose of this study was to investigate the effect of TEAS on the sleep quality in nurses working shift in Kermanshah hospitals. Methods: This study was a single-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In all four studies, the controls received a work rest break similar to that of the intervention group, but without the treatment. One study found the active control ("sham" acupressure points) group also had significant improvements in subjective sleep quality [134]. Further, a significant improvement in blood pressure in the control (reading and resting) group was found in a separate study [132].…”
Section: Complementary Interventionsmentioning
confidence: 95%
See 4 more Smart Citations
“…In all four studies, the controls received a work rest break similar to that of the intervention group, but without the treatment. One study found the active control ("sham" acupressure points) group also had significant improvements in subjective sleep quality [134]. Further, a significant improvement in blood pressure in the control (reading and resting) group was found in a separate study [132].…”
Section: Complementary Interventionsmentioning
confidence: 95%
“…Two studies investigated the effect of massage [131,132], one study investigated the effect of touch therapy [133] and one study investigated the effect of Transcutaneous Electrical Acupoint Stimulation [134]. Half (n = 2) of the studies examined blood pressure changes [132,133] and the other half (n = 2) examined subjective sleep quality [131,134]. One study investigated objective sleep duration [131].…”
Section: Complementary Interventionsmentioning
confidence: 99%
See 3 more Smart Citations